Industry Based on Style Investing and Retail Investors - Mojtaba Soleymani Mareshk; Seyed Abbas Hashemi; Saeed Samadi (تحقیقات مالی, 2017)
Style investing has been developed in behaviral finance literature. In style investing, the investors first classify the investment options based common attribute and then buy their target asset from the selected group. This common attribute is called "style". In this research, the use of "industry" as a style in "style investing" has been survied. Correlation of  retail investors transactions at the industry level was investigated by controlling variables of size and book value to market value. In order to test the research hypotheses, a sample of 8 milions transactions related to 335 firms was selected through a systematic elimination from the listed firms in the Tehran Stock Exchange between 2008 and 2014. The results showed that industry is used as a "style" by retail investors. In addition, the use of size and book value as a "style" was observed.